2017
DOI: 10.2147/nrr.s115555
|View full text |Cite
|
Sign up to set email alerts
|

The courage to be vulnerable: exploring experiences of peer and self-assessment of teaching in nursing education

Abstract: Background: Within academia, more than one measure of assessment is required to ensure teaching success and ongoing teaching development. Peer assessment of teaching is one of the methods that can benefit teaching development; however, there is currently a lack of nursing research literature regarding the processes, outcomes, and use of self-reflection in the peer assessment process. In the spring and summer of 2015, the development and implementation of a tailored pilot project of peer and self-assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(103 reference statements)
1
0
0
Order By: Relevance
“…An additional result, not answering the aim of the study, was that some of the teachers expressed concerns and nervousness about being observed by a colleague. Similar experiences have been discussed previously (Tanner et al, 2017), in terms of vulnerability, in the sense of making individual teaching public for other learners. Another study has shown that fear of criticism can be a barrier for the peer observation process (Adsehead et al, 2006).…”
Section: Högre Utbildning 45supporting
confidence: 69%
“…An additional result, not answering the aim of the study, was that some of the teachers expressed concerns and nervousness about being observed by a colleague. Similar experiences have been discussed previously (Tanner et al, 2017), in terms of vulnerability, in the sense of making individual teaching public for other learners. Another study has shown that fear of criticism can be a barrier for the peer observation process (Adsehead et al, 2006).…”
Section: Högre Utbildning 45supporting
confidence: 69%